Substitusi Tepung Talas Belitung (Xanthosoma sagittifolium) Terhadap Kualitas Fisik dan Mutu Sensoris Nugget Ayam Broiler - Ludfia Windyasmara (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2022)
This study aims to determine the effect of substitution of belitung taro flour (Xanthosoma sagittifolium) on the quality of chicken nuggets, using a completely randomized design (CRD) consisting of 5 treatments with 3 replications and using a duplo sample. The treatment in this study was the substitution of belitung taro flour with a percentage of 0%. 25%. 50%, 75% and 100%. The research data were analyzed using Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) at the level of α = 0.05. The results showed that the substitution of belitung taro flour for broiler chicken nuggets was significantly different (P<0.05) on moisture content, tenderness, and organoleptic tests using color and texture indicators, but not significantly different (P>0.05) on aroma organoleptic tests. and taste. The results of this study concluded that the substitution of belitung taro flour (Xanthosoma sagittifolium) for broiler chicken nuggets affected the moisture content, tenderness and sensory quality on the color and texture indicators of broiler chicken nuggets, but did not affect the sensory quality on the aroma and taste indicators of chicken nuggets. Keywords: Physical quality, Sensory quality, Chicken nuggets, Belitung taro flour.